A Review on Milkweed Fiber Properties as a High-Potential Raw Material in Textile Applications. (February 2017) - Hassanzadeh, Sanaz; Hasani, Hossein
Importance of solving the environmental pollution has attracted lots of designers and engineers' attentions towards finding different available solutions such as substituting polymer-based raw materials with the natural ones. Thus, significant efforts applied by the researchers are generally involved to find new recourses of natural fibers instead of using the petroleum-based synthetic fibers. Among the variety of newly known natural resources, Milkweed is categorized as a versatile substitutive fiber with numerous unique properties which are mainly attributed to their hollowness structures. The presence of hollow channel along the fiber length is responsible for their lightweight and good insulation properties. Because of the fibers' ecological and chemical benefits, numerous technical application fields could be considered for the eco-friendly and non-allergenic textiles made of Milkweed fibers especially in production of medical goods. Since morphological aspects as well as physical and mechanical properties of the Milkweed fibers significantly affect their functional behavior during their end uses, here in this review paper it is aimed to summarize all the available information regarding the fibers' characteristics and properties. Having fundamental knowledge about the spin-ability of Milkweed fibers as well as finding the optimized process condition for their carding operation is considered to be the important points for obtaining such applicable textile products with desired properties.